Patenting Need Of Unique Geographical Indicator Commodities And Products To Enhance Livelihoods And Resources Conservation In Nepal - Paudel, Mina Nath (Agronomy Journal of Nepal, 2021)
This is high time for Nepal to patent endemic genetic resources, commodities and products available in Nepal by studying them scientifically. Nepal is one of the 10th richest countries of Agrobiodiversity availability in Asia and 31st globally. Nonetheless, Nepal being one of the nine oldest countries in Asia, has not been able to harness her potentiality in these areas which could help enhance livelihoods of rural people and gain profit by patenting these resources efficiently. After Prithvi Narayan Shah unified Nepal in 1768 BS, eight countries; Afghanistan, India, China, Korea, Japan, Magnolia, Oman, and Turkey were existed in Asia. The evidences documented in many Vedic and other Sanskrit literatures support Nepal’s existence since time immemorial. This article will help maintain Nepal’s intact for being historically a glorious country since ancient times. Geographical indications (GIs) of crops, commodity and products have special identification of ancientness in Nepal. Bala Chaturdahsi, a unique festival thrived only in Nepal, is an earliest form of genetic resources conservation under Pashupati Nath areas and Shiva temples across Nepal sowing seeds of hundreds of crops since Vedic times. In this article, efforts have been made to document some of the important Nepali cuisine, agricultural commodity, crops, animals, vegetables, fruits, both indigenous and ethnic foods, and products which are very important and endemic to Nepal as GIs with respect to claim their patent rights by Nepal. This article puts efforts to make clear understanding about Nepal with respect to such endemic indigenous genetic resources and their produce locally and globally. It is imperative that Nepal should be in food self-sufficiency and conserve vast pool of unique biodiversity resources and products by patenting them without any delay in days to come.